Preclinical evaluation of eltrombopag in a PDX model of myelodysplastic syndromes - Schmitt, Nanni; Jann, Johann-Christoph; Altrock, Eva; Flach, Johanna; Danner, Justine; Uhlig, Stefanie; Streuer, Alexander; Knaflic, Antje; Riabov, Vladimir; Xu, Qingyu; Mehralivand, Arwin; Palme, Iris; et al. (Leukemia, 2022)
Preclinical research of myelodysplastic syndromes (MDSs) is hampered by a lack of feasible disease models. Previously, we have established a robust patient-derived xenograft (PDX) model for MDS. Here we demonstrate for the first time that this model is applicable as a preclinical platform to address pending clinical questions by interrogating the efficacy and safety of the thrombopoietin receptor agonist eltrombopag. Our preclinical study included n = 49 xenografts generated from n = 9 MDS patient samples. Substance efficacy was evidenced by FACS-based human platelet quantification and clonal bone marrow evolution was reconstructed by serial whole-exome sequencing of the PDX samples. In contrast to clinical trials in humans, this experimental setup allowed vehicle- and replicate-controlled analyses on a patient-individual level deciphering substance-specific effects from natural disease progression. We found that eltrombopag effectively stimulated thrombopoiesis in MDS PDX without adversely affecting the patients’ clonal composition. In conclusion, our MDS PDX model is a useful tool for testing new therapeutic concepts in MDS preceding clinical trials.